Nationale Umsetzung von Cross Compliance (CC) in Deutschland - Breitschuh, Gerhard (Acta agriculturae Slovenica, 2006)
In the paper it is discussion on 19 EU directives, containing 18 basic demandsof EU legislation concerning Cross Compliance (CC). Cross compliance will be implied in the years 2005-2007 in three steps. To avoid diminishing offinancial supports, farmers have to fulfill the demands of CC. It is expected that the need for advisory activities will be intensified. The advisers are able to give to farmers the relevant information on how to fulfill the demands of CC criteria.
Keywords: kmetijska politika; pospeševanje kmetijstva; sistem kontrole; zakonodaja; svetovalna dejavnost